Analysis of Orthotropic RC Rectangular Slabs Supported on Two Adjacent Edges - A Simplistic Approach - Sushant Gupta; Sanjeev Naval (Civil Engineering Journal, 2020)
The design of reinforced concrete slabs supported on two adjacent edges involves complex formulations. In this paper, a simplistic approach is presented for designing orthotropic slabs supported on two adjacent edges. Slab supported on two adjacent edges (existing slab) is transformed into a slab supported on three edges (equivalent slab) by taking a mirror image of the yield line pattern of two adjacent edges supported RC slabs about its unsupported edges to get the exact collapse mechanism for the slabs supported on three edges. The equivalent aspect ratio can be used in the equations already developed for the slabs supported on three sides. Ultimate moment carrying capacity of the slab carrying uniform load can be evaluated by using the available analytical formulations of the slab supported on three edges. So, the present approach gives a simplified method to analyse and design the orthotropic RC rectangular slab supported on two adjacent edges using the equations available for slab supported on three adjacent edges. Hence, the simplistic approach will be very helpful for structural designers dealing with analysis and design of slabs supported on two adjacent edges. Doi: 10.28991/cej-2020-03091598 Full Text: PDF